Trig

posted by .

15^(-x-3)=-17^(-3x) using a log base 10

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Precalculus

    I'm studying for my precalc exam and have completed 42 practice problems. I have 3 I need to answer that I can't. Please help. What is the base of the function G(x) = log subscript b x if it's graph has points (16,4)?
  2. Algebra

    How can you find log base 3 of 242/5 using the given information without a calculator?
  3. algebra 2 logs and trig

    log(base 2)cotx - 2log(base 4)csc2x = log(base 2)cosx the answer should be x = pi/3, 5pi/3 not sure how to work it out though, any help?
  4. math

    mathematically Evaluate without using tables 2 log base 10 raised 2 power 5 + log base 10 36 - log base10 9 that is, 2log10 5 +log 10 36 - log 10 9
  5. Precalc

    1. 1/3log base 8 of (x+1)=2log base 8 of 3-(2/3)log base 8 of (x+1) 2. 2^x+8 times 2^=x all over 2 = 3 3. if log base a of 3= x and log base a of 2 = y, find each of thefollowing in terms of x and y log base a (18a^3) thanks!!
  6. Trig

    log base b 64 - log base b 16 = log base 4 16 solve for the variable.. i got to the part as far as: (log 4/log b) = 2 now i m stuck at how i can isolate the b. plz help!
  7. math

    Use the Laws of logarithms to rewrite the expression log(base 2)(11x(x-9)) in a form with no logarithm of a product, quotient or power. After rewriting we will have: log(base 2)A+log(base 2)x+log(base 2)f(x) What is A and what is f(x)?
  8. Algebra 2

    -Explain the difference between log base b (mn) and ( log base b of m)(log base b of n). Are they equivalent?
  9. Advanced Functions/ Precalculus Log

    1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)x-log(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x-1). …
  10. precalc

    Solve: round to the thousandths if necessary! 1) 4^3/4x+5 = 12 2) log(x-1) + log x = log 6 3) 2log(base 4) 5 - log(base 4) x + log(base 4) 3 - log(base 4) 7 = 1/2

More Similar Questions